Breadwinners and Citizens : Gender in the Making of the French Social Model - Frader, Laura Levine, 1945- (Book collections on Project MUSE., 2008)
Laura Levine Frader advances the argument that the male breadwinner ideal was stronger in France in the interwar years than scholars have typically recognized.